Respuesta :
-9-8(1+4h) = -17. We need to solve for h.
First, use the distributive property for 8(1+4h):
8(1+4h) = 8*1 + 8*4h = 8 + 32h
So -9-8(1+4h) = -17
-9 - (8+32h) = -17
-9 - 8 - 32h = -17
-17 - 32h = - 17
Add 17 on both sides to have the variables on a side and the numbers on the other:
-17 - 32h + 17 = -17 + 17
-32h = 0
divide both sides by -32 to get the variable h alone and its value on the other side:
(-32h)/-32 = 0/-32
h = 0.
So -9-8(1+4h) = -17 for h = 0.
You can recheck your answer (very important):
-9 - 8(1+4h) = -9 -8(1+4*0) = -9 - 8(1+0) = -9-8*1 = -9-8 = -17
The answer has been approved.
Hope this Helps! :)
First, use the distributive property for 8(1+4h):
8(1+4h) = 8*1 + 8*4h = 8 + 32h
So -9-8(1+4h) = -17
-9 - (8+32h) = -17
-9 - 8 - 32h = -17
-17 - 32h = - 17
Add 17 on both sides to have the variables on a side and the numbers on the other:
-17 - 32h + 17 = -17 + 17
-32h = 0
divide both sides by -32 to get the variable h alone and its value on the other side:
(-32h)/-32 = 0/-32
h = 0.
So -9-8(1+4h) = -17 for h = 0.
You can recheck your answer (very important):
-9 - 8(1+4h) = -9 -8(1+4*0) = -9 - 8(1+0) = -9-8*1 = -9-8 = -17
The answer has been approved.
Hope this Helps! :)
Hi Jeannie
-9-8(1+4h) = -17
First, we need to distribute
-9 +(-8)(1) +(-8)(4h) = -17
-9 -8 - 32h = -17
-17 - 32h = -17
-32h = -17 + 17
-32h = 0
h = 0/-32
h = 0
I hope that's help !
-9-8(1+4h) = -17
First, we need to distribute
-9 +(-8)(1) +(-8)(4h) = -17
-9 -8 - 32h = -17
-17 - 32h = -17
-32h = -17 + 17
-32h = 0
h = 0/-32
h = 0
I hope that's help !